Abdominal Masses in Children: A 10-Year Review - Nwokoro CC; Fatungase OM; Salami BA; Shonubi AMO; Adekoya AO; Oyelekan AA (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2015)
Background: Some childhood diseases present with abdominal masses alone or with other constitutional symptoms. The knowledge of the common causes of abdominal masses in children can assist in developing a protocol of management by clinicians. Objective: To describe the aetiology and presentation of abdominal masses in children. Methods: The hospital records of all cases of intra-abdominal masses in children managed between May 1998 and April 2008 were retrieved for analysis. Socio-demographic and clinical data were obtained and analysed using simple descriptive statistics. Results: A total of 93 children were included while those without clinical, radiological and intra-operative evidence of intra-abdominal masses were excluded from the study. There were 49 males (52.7%) and 44 (47.3%) females with male-to-female ratio of 1.1:1. The children were aged 1 day to 14 years; 15 (16.1%) were aged <3 years while 23 (24.7%), 27 (29%) and 14 (15.1%) each were aged 3-6 years, >6-9 years, >9-12 years and >12-14 years. The most common cause of abdominal masses was appendiceal mass/abscess in 29%, followed by hydronephrosis in 22.6% and nephroblastoma in 16.11%. The most common symptoms included abdominal pain (86.0%), fever (46.2%), vomiting (40.9%) and abdominal distension (32.2%). The mortality rate was 13%. Conclusion: Non-malignant conditions were mostly responsible for abdominal masses in children while abdominal pain, fever and vomiting were the leading presentations of abdominal masses in children.